2023
DOI: 10.1161/strokeaha.122.041018
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of Cardioembolic Sources With Nongated Cardiac Computed Tomography Angiography in Acute Stroke: Results From the ENCLOSE Study

Abstract: BACKGROUND: Identifying cardioembolic sources in patients with acute ischemic stroke is important for the choice of secondary prevention strategies. We prospectively investigated the yield of admission (spectral) nongated cardiac computed tomography angiography (CTA) to detect cardioembolic sources in stroke. METHODS: Participants of the ENCLOSE study (Improved Prediction of Recurrent Stroke and Detection of Small Volume Stroke) with transient ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…15,25 While we recognize this may not be comparable to TEE in diagnostic accuracy, we hypothesized that (1) diagnostic images could be possible, as cardiac sources can be detected on non-cardiac CT 26 and (2) findings may improve the detection of embolic sources compared to current standards, as TEE is not routine in etiological workup as per most major guidelines. [9][10][11] Our findings are supported by the ENCLOSE study, 19 which reported a 12% yield of cardiac thrombi in patients with acute stroke or transient ischemic attack.…”
Section: Ccta Feasibility Safety and Utilitysupporting
confidence: 81%
See 1 more Smart Citation
“…15,25 While we recognize this may not be comparable to TEE in diagnostic accuracy, we hypothesized that (1) diagnostic images could be possible, as cardiac sources can be detected on non-cardiac CT 26 and (2) findings may improve the detection of embolic sources compared to current standards, as TEE is not routine in etiological workup as per most major guidelines. [9][10][11] Our findings are supported by the ENCLOSE study, 19 which reported a 12% yield of cardiac thrombi in patients with acute stroke or transient ischemic attack.…”
Section: Ccta Feasibility Safety and Utilitysupporting
confidence: 81%
“…12 In contrast, non-ECG-gated cCTA can be more seamlessly incorporated without significantly increased imaging time or radiation dose and without additional injection of contrast. Recent data have suggested potential utility of non-ECG-gated cCTA in providing diagnostic quality images for detecting high-risk cardioembolic sources, [17][18][19] but needs further investigation and replication.…”
Section: Introductionmentioning
confidence: 99%
“… 18 The ENCLOSE (Improved Prediction of Recurrent Stroke and Detection of Small Volume Stroke) study found that 12% of patients with acute ischemic stroke or transient ischemic attack had cardiac thrombi detected using nongated head‐to‐heart CT angiography, and this rate increased to 32% (27/84) when focusing on patients labeled as cardioembolism. 19 Similarly, Rinkel et al performed ECG‐gated cardiac CT in patients with acute ischemic stroke and identified cardiac thrombus in 8% of them, and this rate increased to 24% (35/143) in patients with cardioembolic stroke. 8 In our study, we focused on patients with acute cardioembolic stroke after reperfusion therapy and used 2‐phase cardiac CT to differentiate thrombus from slow flow effects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, prior anticoagulant therapy was identified as another risk factor for residual cardiac thrombi in our study, which is consistent with the findings of 2 other studies. 8 , 19 This paradox could be partially explained by subtherapeutic international normalized ratio levels in patients treated with vitamin K antagonists. 8 , 19 On the other hand, patients with persistent AF are more likely to be detected during routine clinical assessments compared with those with paroxysmal AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation